Rheumatic Fever Prevention Program: Long-Term Evolution and Outcomes - Mota, Cleonice Carvalho Coelho; Meira, Zilda Maria Alves; Graciano, Rosangela Nicoli; Graciano, Fernando Felipe; Araújo, Fátima Derlene Rocha (Frontiers in Pediatrics, 2015)
This investigation aims to analyze the profile of long term evolution of rheumatic fever in children and adolescents and outcomes after the control of recurrences. The cohort involved 702 patients followed from 1.3 to 16.9 years covering the two periods, before and after the implementation of a prevention program. Besides the establishment of the Reference Center in the State of Minas Gerais and the implementation of strategies to promote the compliance to prophylaxis, a project for education of health professionals was carried out in 23 cities. In addition to the clinical and epidemiological profile, the severity of the disease was analyzed. Mixed lesions were found in 27.1%, valvar regurgitation in 72.9% and complete regression of the valvar lesions was seen in 34.4% of the patients, mostly presenting mild dysfunctions. The recurrence rate per patient-year was 0,058 and out of a total of 85 recurrences, 21,4% occurred in the first and 7,5% in the second period. More severe degrees of carditis and significant valvar sequels presented a higher prevalence in patients with recurrences. The comparative analysis between the two periods showed no changes regarding the age at the primary attack, gender, type and site of valvar lesions and affected joints; however, important modifications in the indices of severity were observed after the control of recurrences. A significant decrease in the prevalence of severe carditis, obstructive valvar sequels, hospital admissions, surgical approach and deaths was seen. This investigation showed that although the clinical profile of presentation remains unchanged, the control of repeated attacks can improve the morbimortality rates. In this context, the secondary prophylaxis should be the first priority in the control of the disease in developing countries, taking into account the difficulties found for effective primordial and primary prevention. Keywords: rheumatic fever, rheumatic heart disease, secondary prophylaxis, recur